2018
DOI: 10.18632/oncotarget.24522
|View full text |Cite
|
Sign up to set email alerts
|

Luminal breast cancer-specific circular RNAs uncovered by a novel tool for data analysis

Abstract: Circular RNAs are highly stable molecules present in all eukaryotes generated by distinct transcript processing. We have exploited poly(A-) RNA-Seq data generated in our lab in MCF-7 breast cancer cells to define a compilation of exonic circRNAs more comprehensive than previously existing lists. Development of a novel computational tool, named CircHunter, allowed us to more accurately characterize circRNAs and to quantitatively evaluate their expression in publicly available RNA-Seq data from breast cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Our research reveals a complex DNA methylationmediated circRNA sponge regulatory mechanism (Supplementary Figure 7). Interestingly, four of the 10 Sponge circRNAs (hsa_circ_000582, hsa_circ_000691, hsa_circ_000877, hsa_circ_000690) were identical to the breast cancer-specific circRNAs from previous studies (Coscujuela Tarrero et al, 2018). Sponge circRNAs may lead to abnormal expression of important protein coding driver genes in breast cancer.…”
Section: Discussionmentioning
confidence: 67%
“…Our research reveals a complex DNA methylationmediated circRNA sponge regulatory mechanism (Supplementary Figure 7). Interestingly, four of the 10 Sponge circRNAs (hsa_circ_000582, hsa_circ_000691, hsa_circ_000877, hsa_circ_000690) were identical to the breast cancer-specific circRNAs from previous studies (Coscujuela Tarrero et al, 2018). Sponge circRNAs may lead to abnormal expression of important protein coding driver genes in breast cancer.…”
Section: Discussionmentioning
confidence: 67%
“…Although a synthetic circRNA construct including an internal ribosome entry site (IRES) can be translated (Wang and Wang 2015), current literature (Jeck et al 2013;Guo et al 2014;Szabo and Salzman 2016;Liang et al 2017;Liu et al 2018;Wang et al 2018;Zeng et al 2018) describes mostly noncoding functions for circRNAs, for example, as miRNA sponge circCDR1 (Hansen et al 2013;Memczak et al 2013;Zhao et al 2015;Kristensen et al 2018) and circZNF91 (Guo et al 2014), whereas associative evidence was reported (Rybak-Wolf et al 2015) of evolutionarily conserved circRNAs between human and mouse. Further support that circRNAs may be specifically generated and regulated was derived from a study using (estrogen-stimulated) MCF-7 cells (Tarrero et al 2018), showing higher levels of H3K36me3 (posttranscriptional histone modification) and a higher number of Ago binding sites in circularizing exons.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 2259 circRNAs (49.9%) were also present in our catalog. In addition, 3271 circRNAs were reported in an MCF-7 breast cancer cell line panel (Tarrero et al 2018). In total, 922 circRNAs showed (increased) expression in estrogen-stimulated MCF-7 cells compared with cells cultured in hormone-deprived medium, of which 733 circRNAs (79.5%) were present in our list.…”
Section: General Characteristicsmentioning
confidence: 96%
“…The development of effective therapies for patients with BC requires the identification of therapeutic and prognostic targets. Recent studies have focused on the identification of differentially expressed non-coding RNAs, including long non-coding RNAs, miRNAs and circRNAs, by gene chip and high-throughput sequencing (44)(45)(46). It is essential to identify early clinical diagnostic markers in order to understand the molecular mechanism underlying, and facilitate the diagnosis of, BC.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq is a common method for genome-wide analysis of circRNAs, though limited by the low reads that cover the specific splicing junction (52). In previous studies, Lan et al (53) investigated circRNA expression profiles via high-throughput RNA-seq in papillary thyroid carcinoma, while Coscujuela et al (45) used RNA-seq to profile and characterize circRNAs in luminal-like BC. Nair et al (44) created a comprehensive workflow termed Circ-Seq based on existing bioinformatics approaches to screen expressed circRNAs in BC subtypes.…”
Section: Discussionmentioning
confidence: 99%